THE EFFECT OF COVID-19 DISRUPTION, RESILIENCE, AND ADAPTATION STRATEGIES ON SUPPLY CHAIN PERFORMANCE (Case Study of Pharmaceutical SOE) - Nisha Nur Aida; Paidi W S; L M Samryn (Management and Leadership Study Programme, 2023)
Abstract The pandemic of COVID-19 caused disruption on supply chain systems, with long-term consequences. The goal of this research is to identify the internal and external factors that cause high vulnerability to disruption and to investigate how COVID-19 disruption, resilience, and adaptation strategies affect supply chain performance (SCP). The research was conducted using qualitative and quantitative approaches, based on a case study at a pharmaceutical company. Document analysis, observation, and interviews were used to collect research data. The techniques and analytical tools used in this study include value chain analysis for internal factor analysis, PESTLE for external factor analysis, and multiple linear regression using Minitab to measure the relationship between variables. The study's findings indicate that internal and external factors influence a company's vulnerability when the COVID-19 disruption occurs. The COVID-19 disruption has had a negative impact on SCP. SCR, SCRM, SCI, and SCE are all components of resilience that have a positive impact on SCP. This research also shows that adaptation strategies such as intertwining, substitution, and repurposing can reduce the impact of pandemic disruptions on SCP and improve it. This study suggests that additional research be conducted on companies with different uniqueness and business processes in order to develop a more complete theory.